QUANTITATIVE ANALYSIS OF BIOACTIVE COMPOUNDS FROM TAGETES ERECTA (LINN.) - R, Devika; Koilpillai, Justin (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: This study investigates the quantitative analysis of the major phytoconstituents of Tagetes erecta (Linn.) and proves their therapeutic value as medicines in both leaf and flower extracts. Methods: The various bioactive compounds were quantitatively analyzed as per standard methods. Results: The present study registered carbohydrates, coumarine, alkaloids, and quinone which are of medicinal importance. During the study, quinone recorded the highest amount of phytocomponents in both the leaf and flower samples. Conclusion: The significant result of the present study revealed that the flower extract exhibited more amounts of phytochemicals than the others, and this could be exploded for potential drug development in future. Keywords: Phytoconstituents, Coumarine, Alkaloids, Quinone, Extraction, Solvents.